Pumiliofossorum: A new genus of Scotobiini (Coleoptera: Tenebrionidae) with two new species from Peru, and a revised key for the genera of the tribe - Silvestro, Violeta A.; Mendoza, Alfredo E. Giraldo; Flores, Gustavo E. (Zootaxa, 2015)
A new genus, Pumiliofossorum Silvestro & Giraldo gen. nov. (Tenebrioninae: Scotobiini) and two new Peruvian species, Pumiliofossorum moche Silvestro & Flores sp. nov. and P. sechurae Giraldo & Flores sp. nov. are described and illustrated. Distributional data, habitat records, photographs, and SEM images are included. A revised key for the six genera of Scotobiini is provided. Morphology of the newly described genus is discussed in reference to the other genera of Scotobiini. Dome-shaped placoid sensoria are imaged for the first time in Scotobiini.